The effect of wirelessly-enabled antepartum maternal-fetal monitoring on patient comfort, labor, and obstetric-neonatal outcomes: A prospective cohort study: Advantages of wireless-enabled prenatal maternal-fetal monitoring - Tekeli Taşkömür, Aysun (Journal of Surgery and Medicine, 2025)
Background/Aim: More than half of perinatal deaths result from stillbirth, with one-third transpiring during the intrapartum period. Therefore, antepartum maternal-fetal monitoring is crucial. This study aims to evaluate the impact of wireless-enabled antepartum maternal-fetal monitoring during labor on enhancing patient comfort, labor duration, and obstetric-neonatal outcomes. Methods: This study employed a prospective cohort methodology. From August 1st, 2021 to August 12th, 2023, 95 pregnant women who initiated active labor were followed using wireless-enabled antepartum maternal-fetal monitoring, and 95 women who used standard cardiotocography during labor. The study included pregnant women who were at least 37 weeks pregnant, had a dilation of 3–4 cm and 50% effacement, no ruptured membrane, and no risky pregnancy conditions (e.g., preeclampsia and HELLP syndrome), and did not use induction methods (e.g., oxytocin). Women who exhibited dilation and effacement beyond these parameters were not included in the study, but those with less were included when they reached these criteria. We compared demographic characteristics, labor duration, movement limitations due to cardiotocography, feelings of discomfort from the probe (assessed using a visual analog scale), and obstetric-neonatal outcomes between the two groups. Results: The groups were homogeneous in terms of demographic characteristics (P>0.05). The average systolic blood pressure, measured every 2 h during childbirth, was higher in the control group (P<0.001). The visual analog scale value associated with continuous wear of the cardiotocography probe and movement restrictions was higher in the control group (P<0.001). Despite a significant difference in birth weeks between the groups (P=0.043), there was no significant difference in birth weights (P=0.373). The duration of labor was shorter in the study group (P=0.011). There was no significant difference in obstetric and neonatal outcomes (P>0.05). Conclusion: Wirelessly-enabled antepartum maternal-fetal monitoring provides greater patient comfort and has a positive impact on labor duration.